Localisation of factor XIII in human tissues using an immunoperoxidase technique. Issue 5 (May 1984) - Fear, J D; Jackson, P; Gray, C; Miloszewski, K J; Losowsky, M S
Abstract : An immunoperoxidase technique has been used to localise clotting factor XIII subunits A and S in human tissues. The presence of factor XIII in placenta and megakaryocytes was confirmed. Factor XIII was also found in fibroblasts, a hitherto unreported finding. Factor XIII subunits were not detected in hepatocytes, although factor XIII was found in fibroblasts in portal tracts. These findings suggest that factor XIII is not synthesised in the liver as previously thought.